Energy Conservation and Energy Management for Industry in Indonesia in Islamic Economic Perspective - Jaelani, Aan; Layaman, Layaman; Fatmasari, Dewi; Salikin, Adang Djumhur; Salam Dz, Abdus (International Journal of Energy Economics and Policy, 2020)
This article will explore energy conservation as part of the national energy policy in Indonesia. Although the government has implemented a strategy for implementing energy conservation by applying energy management to the industrial sector, energy conservation still has challenges and obstacles in making it happen. By analyzing energy conservation policies and understanding the maqasid al-shariah framework which is the operational foundation of Islamic economics on the themes of economic energy, this paper concludes that energy conservation as part of religious obligations implemented in energy consumption behavior, because energy is the main source for sustainability human life. Therefore, moral values become the main foundation in energy conservation behavior as a reflection of the achievement of the objectives of Islamic law and energy management as a systematic effort to utilize energy in industry, not only to increase productivity through energy efficiency and conservation but also to maintain sustainability towards the energy needs themselves. Keywords: energy conservation, energy management, maqashid al-shariah, SDGs, Islamic economics JEL Classifications: O13, P48, Q43, Q48, Q57 DOI: https://doi.org/10.32479/ijeep.9061